Electroless copper seed layer deposition on tantalum nitride barrier film - Chong, S. P. (2012)
Electroless (EL) deposition is used as a seeding technology for Cu metallization in the back-end-of-line semiconductor fabrication process. In this work, effect of deposition time and annealing treatment on the properties of electroless copper seed layer are reported. It is found that all seed layers exceeding 2-min deposition possess a (111) texture. The grain size, morphology and resistivity of the electroless Cu vary with deposition time. The largest grain size obtained by current work is around 70 nm. This corresponds to the lowest resistivity of 4.30 μΩ cm. The surface roughness of as-deposited Cu films ranges from 36.6 to 51.9 nm. Annealing results in the growth of copper grains and improvement in surface roughness and film conductivity. The annealing treatment does not change the existing texture.